Throw a penny in the wishing well [compact disc] - Gasoi, Jennifer (J. Gasoi : Sparkling Productions ; Distributed by Warner Music Canada, 2012)
A collection of eighteen kids' songs. This album contains songs in styles including swing, blue-grass, doo wop, gospel, klezmer, cajun and calypso. Featuring Grammy nominated blues artist Eric Bibb.